Simulation of Surface Plasmon Resonance Biosensor Based on Nanoparticle Coreshell in 633 nm - Widayanti, Widayanti; K, Abraha; A.B, Utomo (Proceeding International Conference on Science and Engineering, 2017)
In this research, we developed the modeling and simulated the biosensor based on Surface Plasmon Resonance (SPR) phenomenon which detected the analyte i.e DNA. This SPR biosensor consists four layers where one of thus layers is the composite material. This nanocomposite spherical nanoparticle consisting of a spherical Fe3O4@Au core covered by Au shell, were applied as active material for DNA detection in 633 nm. Here, we present the simulation of detection amplification technique through Attenuated Total Reflection (ATR) spectrum. Here, SPR system using the Kretschmann configuration, whereas the dielectric function determination of composite coreshell nanoparticle using Effective Medium Theory approximation. Finally, the reflectivity calculation was investigated by varied the size of the core and the shell of the coreshell. The refractive index of the prism is 1,723; the refractive index of 40 nm Ag thin film is 0.13455+3,98651i and the refractive index of the composites were variated dependent the size of nanoparticle coreshell. Our results show that by varying the radius of core and shell thickness, the peak of the reflectivity (ATR spectrum) was shifted to the different angle of incident light. From its result, we can conclude that the addition of coreshell in SPR biosensor leads to enhancement the biosensor sensitivity in DNA detection.